'Naughty' or 'nice' tax avoidance: what is the difference?. (5th January 2011) - Goh, John
This article deals mainly about the difference between unacceptable ('naughty') and acceptable ('nice') tax avoidance, both of which are 'legal'; though for unnaceptable tax avoidance, the HMRC or the courts may deny the tax benefit. Legislative complexity contributes much to the difficulty in ascertaining the distinction between these two forms of tax avoidance. The article explores these difficulties and discusses possible solutions.